From 'literary air hostesses' to 'top bananas': the professional identity of the woman publisher in Australia. - Black, Joshua (Women's History Review, 2026)
Publishing companies (both local independents and multinational conglomerates) play a vital role as merchants of culture, as John Thompson has famously put it. But gender has often been neglected as a crucial category for analysing the business and labour involved in the commercial production of books and print culture. Like so many twentieth-century businesses, Australian publishing companies were often characterised by an overt sexual division of labour, and by hierarchies of career progression that privileged men. Where men often controlled the decision-making processes at the apex of the industry, women's editorial, emotional and entrepreneurial labour remained vital to the construction of its core product: the published book. This article examines the emergence of the woman publisher in twentieth-century Australia as a distinct professional identity within the book publishing industry. It recognises the material and cultural constraints within which that identity was developed and contested. It also accounts for the distinct opportunities that this professional identity afforded women, particularly in the later part of the century. In tracing that story, this article fills an Australia-shaped lacuna in international histories of book publishing and also provides an intellectual bridge between histories of feminism and print capitalism, with relevance beyond Australian scholarship.